Effect of long-chain fatty acids (LCFA) on the prevalence and viability of hydrogenotrophic methanogens - Sousa, D. Z. (2013)
Anaerobic degradation of long-chain fatty acids (LCFA) is essential for efficient biogas production from complex lipid-containing wastewaters. Methanogens play a key role in this process, but the general idea is that LCFA exert a toxic effect towards these microorganisms that impairs good methane recovery. In this work, the effect of saturated (palmitate, C16:0) and unsaturated (oleate, C18:1) LCFA towards hydrogenotrophic methanogens was studied in batch enrichments and in pure cultures. Methanospirillum hungatei and Methanobacterium formicicum were added to oleate- and palmitate-degrading enrichments, cultures OM and PM, and their prevalence was subsequently monitored by PCR-DGGE. M. formicicum grew in both OM and PM cultures, while M. hungatei only prevailed in PM culture. Viability tests using live/dead staining further confirmed that M. hungatei is more sensitive to oleate than M. formicicum. The percentage of damaged cells, caused by the exposure to 0.5 mM of oleate, was higher in M. hungatei cultures (99 ± 1 %) than in M. formicicum cultures (53 ± 10 %). These results suggest that oleate is more inhibitory to methanogens than palmitate, although methane production was not completely inhibited with either LCFA.